Comparison of text-messaging to voice telephone interviews for active surveillance of adverse events following immunisation. Issue 31 (17th July 2015) - Regan, A.K.; Blyth, C.C.; Tracey, L.; Mak, D.B.; Richmond, P.C.; Effler, P.V.
Highlights We compared adverse event information collected by text messages to telephone interview. Response rate was 40% higher to text messages compared to telephone interview. Women were more 60% more likely to report an adverse event by telephone interview. Data collected by text message were significantly timelier. Results indicate text messaging is a feasible method for rapid vaccine safety surveillance.